Effects of supplementation of molassed natural pasture hay with urea, and of water intake restriction on feed intakes by Zebu cattle in the semi-arid zone of Mali - Bartholomew, P.W.; Traoré, B.; Nantoume, H.; Koné, N'G.; Ly, R. (Springer, 1996)
The effects on intake of water availability and urea addition to rations based on molassed natural pasture hay and dry cowpea haulm were measured using 6 mature castrated male Zebu cattle of 343 kg mean iveweight, in an experiment carried out during the dry season in the semi-arid zone of central Mali. The trial was executed and analysed in in which each animal was subject to each of 6 treatments, successively over 6 feeding periods, each of 10 days' duration, throughout which the animals were tied in stalls under shade and fed and watered individually. Natural pasture hay comprising predominantly Pennisetum pedicellatum was fed ad libitum in mixture with 40 percent molasses, with and without addition of urea. Cowpea haulm was fed as a supplement to both diets. Feeding treatments were combined factorially with levels of water allowance. The limited impact of water restriction on feed intake suggests that shortage of drinking water may have a smaller effect on productivity of housed livestock than has been feared, and is an effect which may be compensated for, in the short-term at least by an increase in diet quality.